2010
DOI: 10.1007/s00420-010-0538-y
|View full text |Cite
|
Sign up to set email alerts
|

Job stress models, depressive disorders and work performance of engineers in microelectronics industry

Abstract: The results may provide insight into the applicability of job stress models in a globalized high-tech industry considerably focused in non-Western countries, and the design of workplace preventive strategies for depressive disorders in Asian electronics engineering population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
20
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 52 publications
3
20
0
4
Order By: Relevance
“…A survey of a group of nurses in the ORSOSA study in France identified effort/reward imbalance in 10.7% of the nurses and overcommitment in 40.8% of the nurses 19) . Comparisons of the results of the current study with earlier studies of other occupations in Taiwan show effort/reward ratios of 0.74 (0.22) and 0.97 (0.34) in litigious lawyers and healthy engineers, respectively 2,20) . However, the survey of engineers showed a mean overcommitment score of 14.5 ± 5.2 2) .…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…A survey of a group of nurses in the ORSOSA study in France identified effort/reward imbalance in 10.7% of the nurses and overcommitment in 40.8% of the nurses 19) . Comparisons of the results of the current study with earlier studies of other occupations in Taiwan show effort/reward ratios of 0.74 (0.22) and 0.97 (0.34) in litigious lawyers and healthy engineers, respectively 2,20) . However, the survey of engineers showed a mean overcommitment score of 14.5 ± 5.2 2) .…”
Section: Discussionmentioning
confidence: 49%
“…Comparisons of the results of the current study with earlier studies of other occupations in Taiwan show effort/reward ratios of 0.74 (0.22) and 0.97 (0.34) in litigious lawyers and healthy engineers, respectively 2,20) . However, the survey of engineers showed a mean overcommitment score of 14.5 ± 5.2 2) . In the current study, nurses who worked rotating shifts had a worse mean effort/reward ratio (0.99 ± 0.47) and overcommitment level (16.7 ± 2.84).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Nevertheless, these studies have focused mainly on adverse psychosocial work environment, overcommitment, job strain, and effort-reward imbalance. [12][13][14][15][16][17][18] Currently, little is known about the association between depression and the injury risk magnitude in the context of high biomechanical exposure, physical exposure, and psychological demands. Depression is known to affect work performance, cognitive ability, and workplace hazards monitoring, 8,10,[19][20][21] as well as memory and executive functions.…”
mentioning
confidence: 98%
“…Taiwanese study 88 each reported a high level of job stress among workers in microelectronics. Recently, serial cases of suicide in the Foxconn plants in southern China raised the worldwide concern over the working conditions of microelectronics workers, mostly poor young workers who migrated from rural homes to industrial cities.…”
mentioning
confidence: 99%